The Influence of Teacher Personality Competence, Peers and Social Media on the Consumptive Behavior of Grade XII Students at SMAN 14 Gowa - Nikmawati AR; Syarifuddin; Rego Devilla (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims; 1). To find out and analyze the influence of teacher personality competency on the consumer behavior of class XII students at SMAN 14 Gowa. 2). To find out and analyze the influence of peers on the consumer behavior of class XII students at SMAN 14 Gowa. 3). To find out and analyze the influence of social media on the consumer behavior of class XII students at SMAN 14 Gowa. 4). To find out and analyze the influence of teacher personality competency, peers, and social media simultaneously on the consumer behavior of class XII students at SMAN 14 Gowa. 5). To find out and analyze which variables have the dominant influence on the consumer behavior of class XII students at SMAN 14 Gowa. This research approach uses quantitative research. The research was conducted in Class XII at SMAN 14 Gowa. The population of this research is all students of class XII of SMAN 14 Gowa in the academic year 2025/2026 which consists of 8 classes consisting of Class XII A, XII B, XII C, XII D, XII E and XII F with a population of 288 students. The sampling technique in this study is Purposive Random Sampling, each class XII is represented by 10 students obtained through random per class so that the number of samples is 80 students of class XII. SMA Negeri 14 Gowa, Gowa Regency, data collection techniques using questionnaires and data analysis techniques using multiple regression techniques and t-test analysis and F Test using SPSS 26. The results of this study are; 1). Teacher Personality Competence has a positive and significant effect on the Consumptive Behavior of Class XII Students of SMAN 14 Gowa 2). Peers have a positive and significant influence on the Consumptive Behavior of Class XII Students of SMAN 14 Gowa 3). Social Media has a positive and significant influence on the Consumptive Behavior of Class XII Students of SMAN 14 Gowa 4). Teacher Personality Competence, Peers and Social Media together influence the Consumptive Behavior of Class XII Students of SMAN 14 Gowa 5). The most dominant variable influencing the Consumptive Behavior of Class XII Students of SMAN 14 Gowa is Peers.